Influence of thermomechanical treatments on the microstructure and mechanical properties of AISI 304L welds. (1st February 2023) - Wang, Peng; Szalowski, Bartlomiej; Vallant, Rudolf; Poletti, Cecilia; Enzinger, Norbert
Abstract: A thermomechanical welding (TMW) process is proposed to improve the overall quality of TIG welds by minimizing extensive grain growth or even promoting a fine-grained microstructure. In this study, the welding substrates are tested in three different conditions: as-received (hot-rolled) and cold-rolled with 25% and 50% thickness reduction of AISI 304L plates. The pneumatic hammer is operated with 6 bar pressure and 35 Hz frequency. The results show that the frequent hammering induced two types of vibration on the welds: a) a mechanical vibration and b) the vibration of the TIG arc. Both vibrations combined with the plastic deformation in the solid state refined the solidified microstructure of the fusion zone (FZ), characterized by fine vermicular δ-ferrite with relatively small content. The TIG arc vibration also enlarged the depth of the FZ. Higher hardness was measured on the TMW welds when comparing with the TIG welds without subsequent hammering. The mean grain size of the heat-affected zone (HAZ) was smaller for the material in the cold-rolled condition than in the as-received condition due to martensite reversion and static recrystallization. It is concluded that the proposed TMW process could refine the fusion zone microstructure and hence enhance its mechanical property.